Eksperimentasi Pembelajaran Matematika Dengan Strategi Discovery Learning Dan Problem Based Learning Terhadap Hasil Belajar Matematika Ditinjau Dari Kedisiplinan Siswa (Penelitian Eksperimen Kelas VII SMP Muhammadiyah 4 Surakarta 2014/ 2015) - Mustika Dewi, Enggar, Dr. Sumardi, M.Si (2015)
The purpose of this study was to determine the effect of the difference-based learning strategy Discovery Learning and Problem Based Learning, discipline levels, as well as its interaction with mathematics achievement of students. This study was a quasi-experimental study with a 2 x 3 factorial design with the entire population of eighth grade students of SMP Muhammadiyah Surakarta 4 2014/2015 academic year. Sampling was done by cluster random sampling technique. The sample in this study amounted to 64 students. The research instrument is a test of learning and achievement discipline questionnaire. The test instrument achievement test and discipline questionnaire includes validation, and reliability. Test prerequisites include Lilliefors normality test method and test homogeneity of variance using Bartlett method. Balance test using the self-t. Test the hypothesis using two way analysis of variance with unequal cells. Based on hypothesis testing, research concluded that there are differences in the effects learning model Discovery Learning and Problem Based Learning on mathematics achievement, there are differences in the effect of the level of discipline on mathematics achievement, and there are no interaction Discovery Learning and Problem Based Learning and the level of discipline on mathematics achievement Keywords: Discovery Learning, Discipline, Problem Based Learning.